2010
DOI: 10.1007/s11111-010-0111-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of family planning and other determinants of fertility on population and environment: agent-based modeling evidence from Wolong Nature Reserve, China

Abstract: The practice of family planning has a long history, but its environmental implications have not often been considered. Using data from Wolong Nature Reserve for the conservation of the world-famous giant pandas in China, we employ a spatially explicit agent-based model to simulate how family-planning and other fertility-related decisions may affect human population, household number, and panda habitat over time. Simulation results indicate that (1) population size has the shortest time lag in response to chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…Although this article is based on one published model An and Liu 2010) and one model in review (Zvoleff and An forthcoming), this article is by no means simply a replication of these two models. Recent years have witnessed an increasing number of agent-based modeling applications at different sites and in different contexts (for an ABM review, see An 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Although this article is based on one published model An and Liu 2010) and one model in review (Zvoleff and An forthcoming), this article is by no means simply a replication of these two models. Recent years have witnessed an increasing number of agent-based modeling applications at different sites and in different contexts (for an ABM review, see An 2012).…”
Section: Resultsmentioning
confidence: 99%
“…But unlike a global scenario analysis, regional and local scenario analyses can delve deeper into the workings of coupled systems. Regional and local analyses can go beyond aggregate statistics to explore reciprocal human-nature interactions shaped by social, political, economic, and environmental contexts , An and Liu, 2010, Chen et al, 2012a, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Working in the Wolong Nature Reserve, in China, Liu et al (2003) have shown the influence of household demographics on the landscape, showing that changes in the number of persons per household can be an important determinant of habitat degradation due to household activities such as fuelwood collection (Liu et al 2001, Bearer et al 2008, He et al 2009). Marriage age, family size preferences, and the time between marriage and the first birth (referred to hereafter as "first birth timing") can also affect land cover change, with a time lag between the first changes in marriage age or fertility patterns, and the first observed changes in landscape-level outcomes (An and Liu 2010). VanWey (2003) showed that households in Nang Rong, Thailand pursued temporary migration as a form of income diversification, with the size of land holdings affecting the probability of migration differentially for male and female migrants.…”
Section: Introductionmentioning
confidence: 99%